POSITIONING PENGEMBANGAN DAYA TARIK WISATA KABUPATEN TABANAN MENJADI DESTINASI KREATIF DAN BERKELANJUTAN - Luh Komang Candra Dewi; I Made Bayu Wisnawa; Putu Agus Prayogi (P3M Politeknik Negeri Bali, 2015)
This study entitled Positioning the Development of Tourism Attraction in Tabanan Regency as a Creative and Sustainable Destination, has a background whereas the tourism potential was not touched well in Tabanan Bali in order to be developed into a creative and sustainable tourism destination.This study aims at positioning various tourism attractions existing in tourism destinations in Tabanan therefore each tourisms will examine their own potential, weakness and also competitive profit by developing research model through Multidimensional Scaling (MDS)and Analysis Correspondence (ANACOR) technique using 39 attributes and 22 tourism destinations attractions. Sample in this study usedpurposive and quota sampling technique which consists of foreign tourists, domestic tourists, travel agents, tourism entrepreneurs, the government and academics about 480 people to be asked their perceptions towardpositioning competitive tourism attractions in Tabanan, Bali. Therefore, it can be known the position of each competitive tourisms attraction which are exist in Tabanan, Bali. The instrumentswhich were used,have validity and reliability, where all of the questionnaires with the value of alpha cronbach were over 0.6 (reliable) with the value of acorected item total corelation were over 0.3 (valid). The results of MDS analysis showed that stress coefficients was 0,13462 (13,46%) with RSQ coefficient was 0,89532. The alignment of a model (Delivered Subject Weights) dan scatterplot of linier fit showed the similarity of respondents’ responses towards the objects which were examined. Therefore, tourism attraction in the respondents’ mind were clustered into five groups(i) beach (ii) hot spring, (iii) tourism art and culture, (iv) natural attraction and (v) conservation. The results of ANACORR showed the atributes owned by each tourism attractions which can be classified into four, they are (i) entertainment, (ii) main culture and history (iii) architecture and (iv) scenery. These groups will help the government to develop tourism in Tabanan by regarding the creative potential in the concept of sustainability.The limitation of this study was at too many objects and attributes which had been examined therefore it needed long time. Further research heads for the strategy of developing each group of tourism attraction which has been obtained in this study